Measurable bundles of C*-algebras over ideals - Ganiev, Inomjon; Mukhamedov, Farrukh (Institute of Physics Publishing (UK), 2013)
Let (;§; ¸) be a measurable space with a finite complete measure ¸ and L0 = L0() be an algebra of equivalence classes of complex measurable functions on : In the present paper we define C¤-algebras over ideals of L0: It is proved that any C¤-algebra over ideal can be represented as measurable bundle of C¤-algebras.